A method for preparing high-strength and tough carbon aerogel composite materials through fiber softening effect
By using polyacrylonitrile raw wire as fiber reinforcement in carbon aerogel materials and achieving free shrinkage of the matrix during assisted phase separation and carbonization under high pressure environment, the strength of carbon aerogel materials in high temperature environment is solved. The problems of low and brittleness significantly improve the strength and toughness of the material.
Patent Information
- Application Number
- CN202310520808.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-05-10
AI Technical Summary
The existing carbon aerogel materials have problems such as low strength, high brittleness, matrix cracking and interface debonding in high temperature environments, which limit their practical application.
By using polyacrylonitrile protofilament as fiber reinforcement, the surface-active oxygen-containing functional groups and heat-softening deformation characteristics are used to assist phase separation in high-pressure environments to form a good chemical bonding interface, and realize the resin matrix during the carbonization process. Free shrinkage, reducing residual stress.
It significantly improves the strength and toughness of the composite material, reduces residual stress, avoids problems such as matrix cracking and interface debonding, and improves the overall performance of the material.
Smart Images

Figure BDA0004220763820000081 
Figure HDA0004220763830000011 
Figure HDA0004220763830000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultra-high temperature thermal insulation materials, and in particular to a method for preparing a high-strength and tough carbon aerogel composite material through a fiber softening effect. Background Art
[0002] Aerogel is a porous material stacked by nanoparticles. It has the characteristics of high porosity, large specific surface area, light weight and low thermal conductivity. It has become a new type of thermal insulation material used in many fields. To date, aerogels mainly include: silicon dioxide (SiO2), aluminum oxide (Al2O3) and carbon aerogel. Among them, SiO2 aerogel is the most mature and has been industrialized. However, the surface energy of nano-SiO2 particles is high. When used at high temperatures, particles will sinter, which will cause serious shrinkage of the material volume. Therefore, its long-term use temperature is only 650℃. Compared with SiO2 aerogel, the use temperature of Al2O3 aerogel has been greatly improved, but when it exceeds 1000℃, Al2O3 particles will undergo a crystal transformation, resulting in a serious decrease in its mechanical properties. Carbon aerogel can still maintain its nanoporous structure and mechanical strength above 2000℃ (vacuum or inert atmosphere environment). It is one of the aerogel materials with the best temperature resistance reported today. It is expected to be used as an ultra-high temperature thermal insulation material in various fields such as civil, aviation, and aerospace. However, carbon aerogels generally have problems such as low strength, high brittleness, and easy cracking when prepared in large blocks, which seriously limit their practical applications.
[0003] Practice has proved that introducing a second fiber reinforcement (such as carbon fiber, Al2O3 fiber, mullite fiber, zirconia fiber) into carbon aerogel is the most practical method to improve the toughness and large-scale molding ability of the material. However, experimental results show that although the introduction of the above-mentioned fiber reinforcement can improve the fracture toughness of the material to a certain extent, the prepared material generally has problems such as matrix cracking and fiber / matrix interface debonding, which greatly reduces the mechanical strength of the material. The main reason is that the above-mentioned "rigid" fiber reinforcement does not shrink in volume during the carbonization process, while the organic aerogel matrix (i.e., the precursor of carbon aerogel) shrinks significantly during the carbonization process. The mismatch in shrinkage between the two leads to residual stress inside the material. When the residual stress reaches a certain level, it will cause matrix cracking, interface debonding and other problems. Therefore, how to effectively reduce the residual stress has become the main technical problem faced in the preparation of high-strength and tough fiber-reinforced carbon aerogel composites. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-strength and tough carbon aerogel composite materials through the fiber softening effect. The method is based on the characteristics of polyacrylonitrile precursors with high content of surface active oxygen-containing functional groups and easy softening and deformation when heated. The traditional "rigid" fiber reinforcement is replaced by polyacrylonitrile precursors, and the resin aerogel matrix is synthesized in combination with a high-pressure environment assisted phase separation method. Among them, by utilizing the characteristics of polyacrylonitrile precursors with rich surface active groups, a polymerization reaction between the precursor surface and the resin solution can be achieved during the high-pressure environment assisted phase separation process, thereby forming a good chemical bonding interface between the fiber / matrix. In addition, by utilizing the heat softening and deformation characteristics of polyacrylonitrile precursors, the free shrinkage of the resin matrix during the carbonization process can be achieved, thereby effectively reducing the residual stress inside the material, and fundamentally solving the problems of composite matrix cracking, interface debonding, etc.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a high-strength and tough carbon aerogel composite material through a fiber softening effect comprises the following steps:
[0007] (1) Preparation of resin precursor solution: Resin (PR), solvent (EG), curing agent (H) and pore structure regulator (W) are mixed in a specific ratio and stirred to obtain a resin precursor solution.
[0008] (2) Design and preparation of polyacrylonitrile precursor fiber reinforcement: The fiber mesh composed of polyacrylonitrile precursor is laid layer by layer on the XY plane, and the multiple layers of fiber mesh are sewed in the Z direction by needle punching process to obtain a 2.5D polyacrylonitrile precursor fiber reinforcement.
[0009] (3) Vacuum impregnation of fiber reinforcement: The 2.5D polyacrylonitrile precursor fiber reinforcement obtained in step (2) is placed in a vacuum impregnation tank. When the vacuum degree in the tank reaches the required level, the liquid guide valve is opened, and the resin precursor solution obtained in step (1) is slowly introduced into the vacuum tank. The vacuum pressure is maintained for a certain period of time to allow the resin precursor solution to fully infiltrate the fiber reinforcement.
[0010] (4) High-pressure environment assisted phase separation: The impregnated fiber reinforcement is placed in a curing furnace and filled with inert gas. When the air pressure in the furnace chamber reaches the required level, the temperature is raised and kept warm for a certain period of time. The phase separation reaction of the resin precursor solution is carried out under high temperature and high pressure to obtain a polyacrylonitrile precursor reinforced resin wet gel.
[0011] (5) Drying at normal pressure: placing the wet gel obtained in step (4) in a forced air drying oven and drying it at normal pressure under atmospheric conditions to obtain a polyacrylonitrile precursor reinforced resin dry gel.
[0012] (6) Vacuum carbonization: placing the dry gel obtained in step (5) into a vacuum carbonization furnace for carbonization and cracking to obtain a high-strength and tough polyacrylonitrile-based carbon fiber reinforced carbon aerogel composite material.
[0013] The resin in step (1) is 2130 liquid phenolic resin, whose free phenol content is ≤12wt.%, and solid content is ≥80wt.%; the solvent is ethylene glycol, whose purity is >99%; the curing agent is hexamethylenetetramine, whose purity is >99%; and the pore structure regulating agent is deionized water, whose purity is >99%.
[0014] In the precursor resin solution of step (1), the mass ratio of phenolic resin, ethylene glycol, hexamethylenetetramine and deionized water is 1:(1-4):(0.04-0.16):(0.01-0.32).
[0015] The polyacrylonitrile precursor in step (2) is copolymerized by a comonomer containing a carboxylic acid group (such as acrylic acid, itaconic acid, methacrylic acid, etc.) and acrylonitrile, and has the characteristics of being easily softened and deformed when heated and having a high content of surface active oxygen-containing functional groups.
[0016] The vacuum degree of the vacuum impregnation in step (3) is 50-200 Pa, and the vacuum holding time is 0.5-2h.
[0017] During the high-pressure environment-assisted phase separation process in step (4), the inert gas filled into the furnace is argon or nitrogen. When the atmosphere pressure in the furnace chamber reaches 1-5 MPa, the filling is stopped and the furnace chamber is heated to a temperature of 150-220° C. for 4-16 hours.
[0018] The temperature of the normal pressure drying in step (5) is 60-150° C., and the temperature is kept for 1-3 days.
[0019] The vacuum degree of the vacuum carbonization in step (6) is 100-500 Pa, the heating rate is 5-10° C. / min, the carbonization temperature is 800-1200° C., and the heat preservation time is 4-16 hours.
[0020] The features and advantages of the present invention are as follows:
[0021] 1. The polyacrylonitrile precursor used in the present invention is copolymerized with acrylonitrile by a comonomer containing a carboxylic acid group (such as acrylic acid, itaconic acid, methacrylic acid, etc.), and has the characteristics of high content of surface active oxygen-containing functional groups and easy softening and deformation when heated. Among them, by utilizing the characteristics of rich surface active groups of polyacrylonitrile precursor, polymerization reaction between the precursor surface and the resin solution can be achieved in the process of high pressure environment assisted phase separation, thereby forming a good chemical bonding interface between the fiber / matrix. In addition, by utilizing the characteristics of softening and deformation of polyacrylonitrile precursor when heated, free shrinkage of the organic resin matrix can be achieved during the carbonization process, thereby effectively reducing residual stress, fundamentally solving the problems of matrix cracking and interface debonding, and greatly improving the strength and toughness of the composite material.
[0022] 2. The resin precursor solution in the present invention is composed of phenolic resin, ethylene glycol, hexamethylenetetramine, and deionized water in a specific ratio, and is assisted by high pressure and high temperature during the phase separation process. Under these conditions, hexamethylenetetramine can be decomposed into dimethylolamine, which then undergoes a dehydration condensation reaction with the ortho and para hydrogens of the benzene ring of the phenolic resin to form a carbon-nitrogen bond (CN) with a high degree of cross-linking organic precursor, which is beneficial to the improvement of the intrinsic strength of the gel network. In addition, based on the high boiling point characteristics of ethylene glycol (197.3°C under standard conditions) and the high pressure environment, the release of volatile impurities such as free phenol in the phenolic resin under high temperature conditions and the boiling of the reaction solution can be prevented, thereby providing a stable phase separation reaction environment, which is beneficial to the growth of the gel network and the improvement of structural uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Scanning electron micrographs of the composite material prepared in Example 1; wherein: (a) composite material; (b) and (c) fiber-matrix interfaces at different magnifications; (d) crack propagation path.
[0024] Figure 2 This is a scanning electron micrograph of the composite material prepared in Example 2; wherein: (a) the microscopic morphology of the composite material; (b) the fracture morphology. DETAILED DESCRIPTION
[0025] In order to further understand the present invention, the present invention is described below in conjunction with examples, but the examples are only for further elaboration of the features and advantages of the present invention and are not intended to limit the claims of the present invention.
[0026] The present invention uses polyacrylonitrile precursor as fiber reinforcement, phenolic resin, ethylene glycol, hexamethylenetetramine and deionized water as matrix synthesis raw materials, and successfully prepares a fiber-reinforced carbon aerogel composite material with small residual stress, high toughness, high strength and good thermal insulation performance through vacuum impregnation, high-pressure environment-assisted phase separation, drying and carbonization.
[0027] In the following embodiments, different raw material ratios are used to obtain polyacrylonitrile-based carbon fiber reinforced carbon aerogel composite materials with different properties.
[0028] In the following embodiments, the polyacrylonitrile precursor fiber reinforcement is a fiber web formed by polyacrylonitrile precursor fibers laid layer by layer on the XY plane, and the multi-layer fiber webs are sewn in the Z direction by a needle punching process to obtain a 2.5D polyacrylonitrile precursor fiber reinforcement. The polyacrylonitrile precursor used in the present invention is copolymerized with a comonomer containing a carboxylic acid group (such as acrylic acid, itaconic acid, methacrylic acid, etc.) and acrylonitrile, and has the characteristics of high content of surface active oxygen-containing functional groups and easy softening and deformation when heated.
[0029] Embodiment 1:
[0030] Phenolic resin, ethylene glycol, hexamethylenetetramine and deionized water were mixed in a mass ratio of 3:7:0.4:0.2 and stirred evenly to obtain a resin precursor solution; the polyacrylonitrile precursor fiber reinforcement was cut into the required shape and size and placed in an aluminum alloy mold; the mold with the fiber reinforcement was placed in a vacuum impregnation tank and evacuated; when the vacuum reached 100Pa, the liquid guide valve was opened, and the resin precursor solution was slowly introduced into the vacuum tank, and the vacuum pressure was maintained for 1h to allow the solution to fully infiltrate the fiber reinforcement; the impregnated fiber was placed in a vacuum impregnation tank and the vacuum pressure was maintained for 1h. The fiber-reinforced body is placed in a curing furnace, and nitrogen is filled into the furnace. When the air pressure in the furnace chamber reaches 5MPa, the temperature is raised to 150°C and kept warm for 16 hours to obtain polyacrylonitrile precursor fiber reinforced phenolic wet gel; after demolding, the wet gel is placed in an oven and dried at 120°C under normal pressure for 1 day to obtain polyacrylonitrile precursor fiber reinforced phenolic dry gel; the dry gel is placed in a vacuum carbonization furnace with a furnace chamber vacuum of 200Pa, and the temperature is raised to 900°C at a rate of 5°C / min. After keeping warm for 8 hours, a polyacrylonitrile-based carbon fiber reinforced carbon aerogel composite material is obtained.
[0031] Figure 1 The scanning electron micrograph of the prepared composite material. As can be seen from the figure, the composite material has no microcracks, delamination and other phenomena ( Figure 1 (a)), and the carbon particles are tightly attached to the fiber surface, forming a good chemical interface bonding, e.g. Figure 1 (b) and Figure 1(c). This is related to the rich surface active functional groups of polyacrylonitrile precursor and its softening effect when heated. On the one hand, during the high-pressure assisted phase separation process, the active oxygen-containing groups on the surface of polyacrylonitrile precursor can react chemically with the active sites on the chain of phenolic resin molecules, prompting the phenolic resin solution to nucleate, crosslink and grow on the fiber surface, and then develop into a phenolic aerogel network structure with particle stacking. On the other hand, during the carbonization process, the polyacrylonitrile precursor will soften, allowing the phenolic aerogel matrix to shrink freely, and the phenolic aerogel matrix can also serve as a "support frame" for the polyacrylonitrile precursor, thereby avoiding the problems of melting and agglomeration of the fiber due to the softening effect. The result of the combined effect of the above two aspects is that it can not only significantly reduce the residual stress of the composite material, but also form a good chemical interface bonding between the fiber and the matrix. The fracture toughness of the material was tested by the single-sided notch beam method. It was found that due to the bridging effect of the fiber, the tested material was not completely broken, and the introduction of the fiber could induce crack deflection, and the crack propagation path was "zigzag" and tortuous ( Figure 1 (d)), indicating that the material has good toughness. The test results show that the density of the prepared composite material is 0.6g·cm -3 Its residual stress is only 46MPa (compressive stress) and its fracture toughness is 0.9MPa·m 1 / 2 , compression strength reaches 90MPa, bending strength reaches 30MPa, thermal conductivity is only 0.35W·m -1 ·K -1 The specific performance parameters of the materials are shown in Table 1.
[0032] Embodiment 2:
[0033] Phenolic resin, ethylene glycol, hexamethylenetetramine and deionized water were mixed in a mass ratio of 3:8:0.4:0.1 and stirred evenly to obtain a resin precursor solution; the polyacrylonitrile precursor fiber reinforcement was cut into the required shape and size and placed in an aluminum alloy mold; the mold with the fiber reinforcement was placed in a vacuum impregnation tank and evacuated; when the vacuum reached 100Pa, the liquid guide valve was opened, and the resin precursor solution was slowly introduced into the vacuum tank, and the vacuum pressure was maintained for 1h to allow the solution to fully infiltrate the fiber reinforcement; the impregnated fiber was placed in a vacuum impregnation tank and the vacuum pressure was maintained for 1h. The fiber-reinforced body is placed in a curing furnace, and nitrogen is filled into the furnace. When the air pressure in the furnace chamber reaches 5MPa, the temperature is raised to 150°C and kept warm for 16 hours to obtain polyacrylonitrile precursor fiber reinforced phenolic wet gel; after demolding, the wet gel is placed in an oven and dried at 120°C under normal pressure for 1 day to obtain polyacrylonitrile precursor fiber reinforced phenolic dry gel; the dry gel is placed in a vacuum carbonization furnace with a furnace chamber vacuum of 200Pa, and the temperature is raised to 900°C at a rate of 5°C / min. After keeping warm for 8 hours, a polyacrylonitrile-based carbon fiber reinforced carbon aerogel composite material is obtained.
[0034] Figure 2The scanning electron micrograph of the prepared composite material. As can be seen from the figure, the composite matrix presents a highly developed three-dimensional network structure at the microscopic level, and its particles and pores are distributed very evenly, and there are no defects such as microcracks ( Figure 2 (a)). The reason is that the present invention uses phenolic resin, ethylene glycol, hexamethylenetetramine, and deionized water as the synthetic raw materials of the matrix, and is assisted by high pressure and high temperature in the phase separation process. Under these conditions, hexamethylenetetramine can be decomposed into dimethylolamine, which then undergoes a dehydration condensation reaction with the ortho and para hydrogens of the benzene ring of the phenolic resin to form a CN-bonded, highly cross-linked phenolic aerogel organism, which is beneficial to the improvement of the intrinsic strength of the gel network. In addition, based on the high boiling point characteristics of ethylene glycol (197.3°C under standard conditions) and the high pressure environment, the release of volatile impurities such as free phenol in the phenolic resin under high temperature conditions and the boiling of the reaction solution can be prevented, thereby providing a stable phase separation reaction environment, which is beneficial to the growth of the gel network and the improvement of the structural uniformity. The material exhibits a "rugged" fracture morphology, and obvious fiber pull-out, crack deflection and other phenomena can be observed at its fracture, indicating that the material consumes a large amount of fracture energy during the fracture process ( Figure 2 (b)). The density of the prepared composite material is 0.5 g·cm -3 Its residual stress is only 38MPa (compressive stress) and its fracture toughness is 0.8MPa·m 1 / 2 , compression strength reaches 65MPa, bending strength reaches 25MPa, thermal conductivity is only 0.24W·m -1 ·K -1 The specific performance parameters of the materials are shown in Table 1.
[0035] Comparative Examples 1-4:
[0036] Comparative Examples 1-4 are comparative experiments of Examples 1 and 2, except that phenolic precursor and viscose precursor are used as reinforcements, respectively, and other process parameters remain unchanged. The purpose of implementing Comparative Examples 1-4 is to verify the effect and advantage of the softening effect of polyacrylonitrile precursor. Among them, the reason for choosing phenolic precursor and viscose precursor as comparison is that the above two fibers are also used as reinforcements for carbon aerogels, but these two fibers only shrink in equal proportion during the carbonization process, and no softening deformation occurs. The specific implementation process is as follows: phenolic resin, ethylene glycol, hexamethylenetetramine, and deionized water are mixed in a mass ratio of 3:7:0.4:0.2 (Comparative Example 1, Comparative Example 3) and 3:8:0.4:0.1 (Comparative Example 2, Comparative Example 4), and stirred evenly to obtain a resin precursor solution; phenolic resin or viscose fiber reinforcement is cut into the required shape and size and then placed in an aluminum alloy mold; the mold with the fiber reinforcement is placed in a vacuum impregnation tank and evacuated, and when the vacuum degree reaches 100Pa, the liquid guide valve is opened to slowly introduce the resin precursor solution into the vacuum tank, and the vacuum pressure is maintained for 1h. The solution is fully infiltrated into the fiber reinforcement; the impregnated fiber reinforcement is placed in a curing furnace, and nitrogen is filled into the furnace. When the pressure in the furnace chamber reaches 5MPa, the temperature is raised to 150°C and kept warm for 16 hours to obtain phenolic or viscose fiber reinforced phenolic wet gel; after demoulding, the wet gel is placed in an oven and dried at 120°C at normal pressure for 1 day to obtain phenolic or viscose fiber reinforced phenolic dry gel; the dry gel is placed in a carbonization furnace, and the temperature is raised to 900°C at a rate of 5°C / min under a vacuum degree of 200Pa, and after keeping warm for 8 hours, a phenolic-based carbon fiber or viscose-based carbon fiber reinforced carbon aerogel composite material is obtained. The specific performance parameters of the material are shown in Table 1.
[0037] As can be seen from Table 1, the residual stress of the composite material prepared by using polyacrylonitrile precursor as reinforcement (Example 1: 46MPa, Example 2: 38MPa) is significantly lower than the residual stress of the composite material in the comparative example (Comparative example 1: 906MPa, Comparative example 2: 680MPa, Comparative example 3: 272MPa, Comparative example 4: 230MPa). Due to the significant reduction in residual stress, the composite material in the present invention exhibits higher fracture toughness, bending strength, and compressive strength, and its specific bending strength and specific compressive strength can reach 50 and 150MPa·g respectively. -1 cm 3 , which is significantly higher than that of the other two composite materials.
[0038] Table 1. Performance parameters of the composite materials prepared in Examples 1-2 and Comparative Examples 1-4
[0039]
Claims
1. A method for preparing a high-strength and tough carbon aerogel composite material through a fiber softening effect, characterized in that: The method specifically comprises the following steps: (1) Preparation of resin precursor solution: resin (PR), solvent (EG), curing agent (H) and pore structure regulator (W) are mixed in a specific proportion and stirred to obtain a resin precursor solution; (2) Design and preparation of polyacrylonitrile precursor fiber reinforcement: A fiber mesh composed of polyacrylonitrile precursor is laid layer by layer on the XY plane, and the laid multi-layer fiber mesh is stitched in the Z direction by a needle punching process to obtain a 2.5D polyacrylonitrile precursor fiber reinforcement; (3) Vacuum impregnation of fiber reinforcement: the 2.5D polyacrylonitrile precursor fiber reinforcement obtained in step (2) is placed in a vacuum impregnation tank. When the vacuum degree in the tank reaches the required level, the liquid guide valve is opened to slowly introduce the resin precursor solution obtained in step (1) into the vacuum tank, and the vacuum pressure is maintained for a certain period of time to allow the resin precursor solution to fully infiltrate the fiber reinforcement; (4) High-pressure environment assisted phase separation: The impregnated fiber reinforcement is placed in a curing furnace and filled with inert gas. When the pressure in the furnace chamber reaches the required level, the temperature is raised and kept warm for a certain period of time. The phase separation reaction of the resin precursor solution is carried out under high temperature and high pressure to obtain a wet gel of polyacrylonitrile precursor reinforced resin. (5) Drying at normal pressure: placing the wet gel obtained in step (4) in a forced air drying oven and drying it at normal pressure under atmospheric conditions to obtain a polyacrylonitrile precursor reinforced resin dry gel; (6) Vacuum carbonization: placing the dry gel obtained in step (5) into a vacuum carbonization furnace for carbonization and cracking to obtain a high-strength and tough polyacrylonitrile-based carbon fiber reinforced carbon aerogel composite material; The resin in step (1) is 2130 liquid phenolic resin, whose free phenol content is ≤12wt.%, and solid content is ≥80wt.%; the solvent is ethylene glycol, whose purity is >99%; the curing agent is hexamethylenetetramine, whose purity is >99%; the pore structure regulator is deionized water, whose purity is >99%; In the precursor resin solution of step (1), the mass ratio of phenolic resin, ethylene glycol, hexamethylenetetramine and deionized water is 1: (1-4): (0.04-0.16): (0.01-0.32); The polyacrylonitrile precursor in step (2) is copolymerized with acrylonitrile and a comonomer containing a carboxylic acid group, and has the characteristics of high content of surface active oxygen-containing functional groups and easy softening and deformation when heated. The comonomer containing a carboxylic acid group is acrylic acid, itaconic acid, and methacrylic acid. The vacuum degree of the vacuum impregnation in step (3) is 50-200 Pa, and the vacuum holding time is 0.5-2 h; The vacuum degree of the vacuum carbonization in step (6) is 100-500 Pa, the heating rate is 5-10 °C / min, the carbonization temperature is 800-1200 °C, and the heat preservation time is 4-16 h.
2. The method for preparing high-strength and tough carbon aerogel composite material by fiber softening effect according to claim 1, characterized in that: During the high-pressure environment-assisted phase separation process in step (4), the inert gas filled into the furnace is argon or nitrogen. When the atmosphere pressure in the furnace chamber reaches 1-5 MPa, the filling is stopped and the furnace chamber is heated to a temperature of 150-220°C for 4-16 hours.
3. The method for preparing high-strength and tough carbon aerogel composite material by fiber softening effect according to claim 1, characterized in that: The temperature of the normal pressure drying in step (5) is 60-150°C, and the temperature is kept for 1-3 days.
4. The method for preparing high-strength and tough carbon aerogel composite material by fiber softening effect according to claim 1, characterized in that: When the material density is 0.6 g cm -3 When the residual stress is 46 MPa, the fracture toughness is 0.9 MPa m 1 / 2 , compressive strength is 90 MPa, flexural strength is 30 MPa, thermal conductivity is 0.35 W m -1 K -1 .
Citation Information
Patent Citations
Preparation method of low-cost and high-strength fiber-reinforced nano porous carbon composite material
CN112341234A